Institutionalization and Rehabilitation of Street Children in Benue State - E. M, Kembe; L. E., Okonkwo (Journal of Home Economics Research, 2024)
The study investigated institutionalization and rehabilitation of street children in Benue State. A Cross Sectional research design was used to conduct the study. Data was collected using two sets of questionnaires for staff and orphans, (Rehabilitation Staff Questionnaire, RSQ and Rehabilitation Orphan Questionnaire, RIQ). Two hypotheses were formulated and analyzed using mean and standard deviation. Finding show causative factors like poverty,(3.20),Abandonment(3.10), death of parents ( 2.20), divorce and remarriage (2.17) being responsible for street children and rehabilitation of children. Findings also showed a number of problems in these institutions to include late feeding (3.18), harsh punishment (3.03), in fighting amongst the orphans (2.95)) and liaise – faire attitude of the workers, (2.97).On the state of infrastructure and facilities, result shows that storage facilities and access road network represents 3.74 and 2.58 respectively, while, the environment and water recorded 2.28 and 2.20 respectively. On the programs for rehabilitation, all ten (10) programs scored below the acceptable mean of 2.00, which means performance was below expectations or these programs were minimally being carried out. Based on the findings, it was concluded that institutions for children rescued out of the street will continue to serve as alternative care centers for children, though, there are inherent problems that require interventions from the government, staff training and the involvement of NGOS and CBOS.